2016
DOI: 10.1128/jvi.00407-16
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free versus Cell-to-Cell Infection by Human Immunodeficiency Virus Type 1 and Human T-Lymphotropic Virus Type 1: Exploring the Link among Viral Source, Viral Trafficking, and Viral Replication

Abstract: Human immunodeficiency virus type 1 (HIV-1) and human T-lymphotropic virus type 1 (HTLV-1) are complex retroviruses mainly infecting CD4؉ T lymphocytes. In addition, antigen-presenting cells such as dendritic cells (DCs) are targeted in vivo by both viruses, although to a lesser extent. Interaction of HIV-1 with DCs plays a key role in viral dissemination from the mucosa to CD4؉ T lymphocytes present in lymphoid organs. While similar mechanisms may occur for HTLV-1 as well, most HTLV-1 data were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 135 publications
(183 reference statements)
0
46
0
1
Order By: Relevance
“…This route allows the barriers of multistep receptor binding to be avoided and helps to protect viruses from the host immune response. There is growing evidence that for some human pathogens, such as HIV and human T cell leukemia virus type 1 (HTLV-1), cell-to-cell spread appears to be the main mode of dissemination, not only within the infected host but also between hosts (41)(42)(43). For herpesviruses, which use multiple strategies to spread, including transmission between cells via tight junctions, filopodia, and virological synapses, direct cell-to-cell spread is an important immune-evasive strategy contributing to the capacity of this virus to survive after reactivation, when the virus is confronted with immune defenses developed during the primary infection (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…This route allows the barriers of multistep receptor binding to be avoided and helps to protect viruses from the host immune response. There is growing evidence that for some human pathogens, such as HIV and human T cell leukemia virus type 1 (HTLV-1), cell-to-cell spread appears to be the main mode of dissemination, not only within the infected host but also between hosts (41)(42)(43). For herpesviruses, which use multiple strategies to spread, including transmission between cells via tight junctions, filopodia, and virological synapses, direct cell-to-cell spread is an important immune-evasive strategy contributing to the capacity of this virus to survive after reactivation, when the virus is confronted with immune defenses developed during the primary infection (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Actually thalidomide and pentoxyfilline, drugs known to decrease TNF production, attenuate clinical manifestations of Erythema nodosum in patients with lepromatosus leprae [28,29]. The HTLV-1 infects a variety of immune cells as TCD4, TCD8, B cells, macrophages and dendritic cells [30]. As the Tax gene of the virus transactivates human genes in infected cells, HTLV-1 is associated with high production of pro-inflammatory cytokines such as TNF, IFN-γ, IL-1 and IL-6 [31].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes are not the only cell type that HTLV-1 is able to infect. It has been reported that HTLV-1 can also infect monocytes/macrophages and dendritic cells [68][69][70][71][72][73][74][75][76], but their role in viral pathogenesis is not fully understood. In infected individuals, the majority of viral DNA is found in CD4 + and CD8 + T-cells.…”
Section: The P30 Protein Inhibits the Interferon Responsementioning
confidence: 99%